A Reflection on the State of Multisensory Human–Food Interaction Research - Velasco, Carlos; Wang, Qian Janice; Obrist, Marianna; Nijholt, Anton (Frontiers in Computer Science, 2021)
We present a perspective article on the state of multisensory human–food interaction (MHFI) research and lay out some reflections for research and development in this area of inquiry, based on a revision of the different spaces that we have co-created with researchers in this space. We begin by conceptualizing and defining MHFI, before moving onto presenting some of its major themes, as well as possible ways in which such themes can guide future research in the area. This article provides key definitions and foundations for the area of MHFI, as well as a first point of contact for those interested in it.